Development and Testing of Arduino-Based Virus Spread Prevention Tools - Khairul Imtihan; Wire Bagye; Maulana Ashari (STMIK Budi Darma, 2024)
The process of online buying and selling transactions which are global in nature by involving many people actually facilitates the process of spreading viruses, one of which is the Covid-19 virus, which spreads mostly through splashes of liquid expelled from the nose and mouth, such as sneezing, coughing and yawning. Viruses that stick to the surface of goods also have the potential to infect humans who come in direct contact. The incubation period for the virus until the disease appears is between 3 (three) to 7 (seven) days. the covid-19 virus is sensitive to heat with a temperature of 56 ? for 30 minutes. Based on the root of the problem, this research was conducted as an effort to prevent the chain of distribution of Covid-19 by building a heating box with a width of 50 cm and a length of 65 cm using fiber glass material with a thickness of 3mm. By using Arduino Uno as a tool to control the MLX temperature sensor, the temperature sensor works by emitting infrared light towards the surface of the goods wall, then reflected and received by the receiver. This heat will be converted by the temperature sensor module into a voltage between 0 to 5 Volts.This voltage is used as an arduino input to get the surface temperature of goods, the results of temperature readings are displayed on the 16 x 2 LCD. Based on the validation results of the electronic circuit design and heating box, validation results obtained were 89.26% for usability, 86.96% for information quality and 92.2% for service interaction quality with an average percentage of 89.47%, which means the tool is running well. The test results using an initial temperature of 30ºC and the desired temperature of 56ºC takes 1 minute 13 seconds, the temperature displayed on the LCD has reached 56ºC. . This heater is also operated through an android application that communicates with the Arduino microcontroller via the HC-05 bluetooth moduleAbstract is a brief summary of the manuscript to help readers quickly determine the main research problem, the method used as a solution to solving the problems encountered, research objectives and temporary research results which can be in the form of numbers/percentages according to research needs. The abstract should be clear and informative, providing a statement for the problem under study. Abstract length between 200 to 230 words. The abstract has no citations/references. Avoid unusual abbreviations and define all symbols used in the abstract. Using keywords related to the research topic is recommended.